Social Distancing: Prevalence of Depressive, Anxiety, and Stress Symptoms Among Brazilian Students During the COVID-19 Pandemic - Esteves, Cristiane Silva; Oliveira, Camila Rosa de; Argimon, Irani Iracema de Lima (Frontiers in Public Health, 2021)
Social distancing due to the COVID-19 pandemic can impact mental health, triggering symptoms such as anxiety, stress and depression. Therefore, this study aimed to verify the levels of anxiety, depression and stress during the period of social distancing due to COVID-19 in students from a campus of the Federal Institute in the metropolitan area of Porto Alegre/RS. A quantitative, descriptive, correlational and exploratory study was performed. Participated in the study 208 students, who responded to a self-administered online questionnaire with sociodemographic variables and the Depression, Anxiety and Stress Scale Short Form – DASS-21. Considering moderate and severe intensities, the stress symptoms presented the highest prevalence (49%), followed by depression symptoms (39%) and anxiety symptoms (33%). There was an association between anxiety symptoms and study activities (X2 = 6.487; p = 0.039), and students with absence or minimum levels of anxiety maintained less engagement in study activities. Furthermore, there was an association between higher levels of anxiety symptoms (X2 = 27.848; p < 0,001), depression (X2 = 15.871; p < 0,001) and stress (X2 = 36.904; p < 0,001) regarding the occurrence of sleep during the period of social distancing. These data are extremely important for understanding the adverse effect on the mental health of students and for developing psychological support strategies, thus promoting well-being during and after the pandemic.